The crosstalk of caveolin-1 and autophagy in different diseases - Yang, Yuting; Ma, Qiqi; Yang, Mei; Wei, Ruixue; Wang, Zhiguo; Jiang, Chunmeng; Liu, Hui; Han, Mei (Frontiers in Immunology, 2025)
Caveolin-1 (Cav-1) is an important structural protein that constitutes the caveolae on the cell membrane. Cav-1 is expressed in various cells, especially in white adipocytes and endothelial cells. Cav-1 plays an important physiological role in regulating substance transport, signal transduction, and multiple metabolic pathways in the body. Autophagy degrades damaged organelles within cells and recycles them, thus playing an important role in maintaining homeostasis of the internal environment. Previous studies have found that Cav-1 is involved in the occurrence and development of multiple systemic diseases by regulating autophagy. In addition, autophagy can also affect the expression level of Cav-1 by degrading it. Therefore, there is a close regulatory relationship between Cav-1 and autophagy. Based on recent research progress, this article provides a detailed overview of the importance of the crosstalk between Cav-1 and autophagy in various systemic diseases such as cardiovascular, respiratory, and digestive systems. It aims to provide a more comprehensive understanding of the interaction between Cav-1 and autophagy, in order to promote further research and achieve clinical applications as soon as possible.